Presença das línguas chinesas e integração de chineses em diversos espaços sociais de Foz do Iguaçu – PR: um estudo interdisciplinar - Yu, Michele Siu Mui (2018)
This dissertation proposes, as a general objective, to investigate the presence of Chinese groups in Foz do Iguaçu - PR and their relations with local society. The research was developed from an interdisciplinary perspective, based on field of Language Policy, which aims to understand the decisions and relations between languages and society. As for the methodology, the research approach is qualitative and uses several interpretative procedures to understand how the integration experiences lived by the research subjects are configured. Regarding the means of obtaining data, the research was preceded by bibliographic research, followed by field observation and structured interviews. The data reveal that the presence of Chinese writing in public spaces in the city of Foz do Iguaçu is mainly evidenced in commercial establishments aimed at the Chinese community and restaurants specializing in Chinese cuisine. It was verified that, except for the Buddhist temple, the places where the Chinese writing was observed were in the central region of Foz do Iguaçu. Concerning integration, data suggests that there were behaviours of social isolation and little integration with the local community of Foz do Iguaçu. Based on the results, suggestions are made to improve the integration of the Chinese community and to bridge the linguistic borders, such as the insertion of essential information in the Chinese language in the main public services, as well as the proposal of public educational policies for teaching-learning Portuguese language to immigrants. It is expected that this research will contribute to giving visibility to the Chinese languages, as well as indicating ways to decrease the linguistic and cultural border between the Chinese language speakers and local community in the Foz do Iguaçu border context.